Making relativistic positrons using ultraintense short pulse lasers - Chen, H; Wilks, S; Bonlie, J; Chen, SN; Cone, K; Elberson, L; Gregori, G; Meyerhofer, D; Myatt, J; Price, D; Schneider, M; Shepherd, R; et al. (2009)
This paper describes a new positron source using ultraintense short pulse lasers. Although it has been theoretically studied since the 1970s, the use of lasers as a valuable new positron source was not demonstrated experimentally until recent years, when the petawatt-class short pulse lasers were developed. In 2008 and 2009, in a series of experiments performed at the Lawrence Livermore National Laboratory, a large number of positrons were observed after shooting a millimeter thick solid gold target. Up to 2× 1010 positrons/s ejected at the back of approximately millimeter thick gold targets were detected. The targets were illuminated with short (∼1 ps) ultraintense (∼1× 1020 W/ cm2) laser pulses. These positrons are produced predominantly by the Bethe-Heitler process and have an effective temperature of 2-4 MeV, with the distribution peaking at 4-7 MeV. The angular distribution of the positrons is anisotropic. For a wide range of applications, this new laser-based positron source with its unique characteristics may complement the existing sources based on radioactive isotopes and accelerators. © 2009 American Institute of Physics.